2020
DOI: 10.1186/s13195-020-00636-z
|View full text |Cite
|
Sign up to set email alerts
|

The dynamics of biomarkers across the clinical spectrum of Alzheimer’s disease

Abstract: Background: Quantifying changes in the levels of biological and cognitive markers prior to the clinical presentation of Alzheimer's disease (AD) will provide a template for understanding the underlying aetiology of the clinical syndrome and, concomitantly, for improving early diagnosis, clinical trial recruitment and treatment assessment. This study aims to characterise continuous changes of such markers and determine their rate of change and temporal order throughout the AD continuum. Methods: The methodology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
78
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(84 citation statements)
references
References 71 publications
6
78
0
Order By: Relevance
“…Theta also showed separation between low cognitive load and resting state. This is in line with previous reports of frontal Theta and Delta increase during cognitively demanding tasks [36]–[38]. This difference was not present in the senior population, supporting the notion that Theta and Delta may be indicative to cognitive decline and serve as a predictor of deterioration status, consistent with previous findings [10], [11].…”
Section: Discussionsupporting
confidence: 93%
“…Theta also showed separation between low cognitive load and resting state. This is in line with previous reports of frontal Theta and Delta increase during cognitively demanding tasks [36]–[38]. This difference was not present in the senior population, supporting the notion that Theta and Delta may be indicative to cognitive decline and serve as a predictor of deterioration status, consistent with previous findings [10], [11].…”
Section: Discussionsupporting
confidence: 93%
“…It was shown that cognitive decline is associated with high-risk for developing dementia, and Alzheimer's disease in particular [2], and that cognitive decline may be detected several years before dementia onset with known validated tools [39]. Dementia is gradually recognized as one of the most signi cant medical challenges of the future.…”
Section: Discussionmentioning
confidence: 99%
“…Absolute power values were converted to logarithm base 10 to produce values in dB. The following frequency bands were included: Delta (0.5-4 Hz), Theta (4-7 Hz), Alpha (8-15 Hz), Beta (16-31 Hz), and lower Gamma (32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45). The BAFs analysis included the activity of the three selected biomarkers: ST4, A0, and VC9 normalized to a scale of 0-100.…”
Section: Electrophysiological Variablesmentioning
confidence: 99%
“…These early signs of cognitive decline are followed by abnormal changes in Aβ1-42 cerebrospinal fluid (CSF) levels and concurrent hippocampal atrophy. More than a decade after the first signs of memory dys- function, brain hypometabolism develops, accompanied by abnormal changes in total and phosphorylated tau proteins levels [ 62 ]. These conclusions are consistent with the study of predicting time to dementia in AD patients participating in the Neuroimaging Initiative that reported early changes in verbal memory, CSF Aβ1–42, and hippocampal volume [ 63 ].…”
Section: Discussionmentioning
confidence: 99%